2019
DOI: 10.1007/s00415-019-09493-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise improves quality of life, depressive symptoms, and cognition across chronic brain disorders: a transdiagnostic systematic review and meta-analysis of randomized controlled trials

Abstract: We performed a meta-analysis to synthesize evidence on the efficacy and safety of physical exercise as an add-on therapeutic intervention for quality of life (QoL), depressive symptoms and cognition across six chronic brain disorders: Alzheimer's disease, Huntington's disease, multiple sclerosis, Parkinson's disease, schizophrenia and unipolar depression. 122 studies (= k) (n = 7231) were included. Exercise was superior to treatment as usual in improving QoL (k = 64, n = 4334, ES = 0.40, p < 0.0001), depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 237 publications
3
91
2
3
Order By: Relevance
“…MET is an index of energy expenditure that results from IPAQ‐SF, a commonly used questionnaire to assess quantitatively physical activity, even in PD 8,10 . A higher rate of physical activity improves quality of life, mood, and cognitive performances, and even motor disturbances in PD patients, exerting beneficial effects either at brain or systemic level 8,11,12 . The reduction of such “protective” action might thus explain the perception of worsening in these patients, which also presented a greater burden of PD‐related disturbances (PWBM score) and depressive symptoms (BDI score) compared to those referring stable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…MET is an index of energy expenditure that results from IPAQ‐SF, a commonly used questionnaire to assess quantitatively physical activity, even in PD 8,10 . A higher rate of physical activity improves quality of life, mood, and cognitive performances, and even motor disturbances in PD patients, exerting beneficial effects either at brain or systemic level 8,11,12 . The reduction of such “protective” action might thus explain the perception of worsening in these patients, which also presented a greater burden of PD‐related disturbances (PWBM score) and depressive symptoms (BDI score) compared to those referring stable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Rather different physical exercise interventions had all positive clinical effects in patients with schizophrenia, unipolar depression, Alzheimer's disease, Huntington's disease, Parkinson's disease, and multiple sclerosis. 90 Many professionals state that the prescription of physical activity interventions should be placed on a par with drug prescription, but this implies that neuropsychiatrists "know how to prescribe, monitor, and evaluate the effectiveness of the exercise prescribed". 91 However, this is not often the case and this obstacle must be overcome by the multidisciplinary approach with the support of the exercise trainer.…”
Section: Practical Suggestions To Promote Physical Activitymentioning
confidence: 99%
“…The role of physical activity in improving the QoL has been demonstrated in various diseases. Recently, a meta-analysis conducted in six chronic brain disorders (Parkinson's disease, Alzheimer's disease, Huntington's disease, multiple sclerosis, schizophrenia, and unipolar depression) confirmed that exercise is superior to pharmacological treatment in improving QoL (Dauwan et al, 2019). The maintenance of QoL found in this study in individuals with ALS who exercised, and the tendency toward lower values of QoL in individuals with ALS who did not exercise, is probably due to the fact that participants in the TRAIN group felt that their motor skills were maintained and that they could do something about it.…”
Section: Discussionmentioning
confidence: 99%